PEMBINAAN AKHLAK SISWA MELALUI PEMBELAJARAN PAI DI SMP ISLAM PAKIS KABUPATEN MALANG - Muhammad Iqbal A'ufillah; Azhar Haq; Dwi Fitri Wiyono (VICRATINA, 2021)
In the midst of an instantaneous and increasingly popular modernization era, Muslims are now more focused on getting worldly pleasures rather than promoting the value of Islam as the power of faith to receive the grace of Allah SWT. Not infrequently, as we know, the life of the Muslim youth today shows as if morals and good behavior are not important. Although in terms of educational facilities, print and electronic media, clothing, mosques, the quality of religious experts and even da'wah activities that are increasingly advanced and developing, this development is largely influenced by the modernization of Western-style Science and Technology. Kata Kunci: Moral Development, learning PAI